Case study of a neuroendocrine tumor of uncertain origin: single-cell transcriptomics unravels potential primary location - Frolova Tatyana; Ekaterina Avsievich; Diana Salimgereeva; Zoia Antysheva; Alesia Maluchenko; Denis Maksimov; Ilia Feidorov; Mark Voloshin; Olga Glazova; Natalia Bodunova; Nikolay Karnaukhov; Pavel Volchkov; et al. (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Determining the primary origin of non-organ-confined neuroendocrine tumors (NETs) for accurate diagnosis and management. Neuroendocrine tumors are rare neoplasms with diverse clinical behaviors. Determining their primary origin remains challenging in cases of non-organ-confined NETs. This study explores the histogenesis of a retroperitoneal, non-functional NET localized between the duodenum and pancreatic head, utilizing advanced molecular diagnostics to elucidate its probable primary source. Methods Initial diagnostic methods, including imaging and histopathology, failed to resolve the tumor’s origin. The tumor was subjected to single-cell RNA sequencing (scRNA-seq) and whole exome sequencing (WES). Publicly available transcriptomic datasets from pancreatic and small intestine NETs were used to develop and validate a molecular gene signature for tissue-of-origin identification. Results The gene signature distinguished pancreatic and small intestine NETs with high accuracy. The tumor cells presented a molecular profile consistent with a pancreatic origin, likely derived from ectopic pancreatic tissue. Conclusions This case demonstrates the value of integrating scRNA-seq and WES for the molecular characterization of complex NETs. Identifying the tumor’s pancreatic origin informed a targeted management approach, avoiding unnecessary systemic treatment and underscoring the potential of single-cell approaches in personalized oncology.